Plan ahead by embracing retrospective approach: global health - Saxena, Arpita (International Journal Of Community Medicine And Public Health, 2020)
Many countries worldwide are experiencing a see-saw pattern in health sector as individuals demand for health services rise exponentially during their fear and anxiety of disease and death. But medical care alone cannot bring health (physical/mental) to people living in rural/urban areas. It is the blending of natural and man-made variables to overcome poverty, unemployment, poor sanitation, and, not to be excused, ailing health. It is likely to expect significant health improvements in those respective areas if given a radical approach. To address the needs of public, World Health Organization came up with some strategies to improve health guidelines, reduce health risks, to have immense progress and to support a sound lifestyle to every human in 1970s that were to be fulfilled by 2000. The term ‘Health for All’ was defined in 1981 in which its goals were interlinked with each other in some or the other way. For instance, to reduce crude death rate, some eradication programmes were being improvised and at the same time those programmes helped to increase life expectancy of individuals by improving quality of life. To put it in a nutshell, public health has always been a key factor of all time since the beginning of the universe, we need to realize that to diminish health inequalities, we have to amalgamate ancient and advanced technology in an effective pattern to improve health and address health issues as they begin to develop.